Mental Health and Coping Stress: A Study in Talang Lahat Village, Curup Bengkulu - Badriyah, Lailatul; Haryati, Asti; Ramos, Sarah V. (Universitas Muhammadiyah Metro, 2023)
This article aims to present the research results on the analysis of the mental health of vegetable farmers in terms of coping with stress. The condition of crop failure is something that all farmers do not expect, but this condition cannot be predicted because it depends on natural factors. One of the stresses that arise when a crop failure occurs is disappointment, lack of financial capital, feeling a heavy burden, and harboring many desires that cannot be realized. This research used a mixed-method approach (quantitative and qualitative). The research sample consisted of 25 productive farmers in a Talang Lahat Curup Bengkulu Village farmer group. The results showed that coping stress was positively correlated and tended to be high (r(25)=0.515; p<0.008) with the mental health of vegetable farmers. The simple linear regression test shows that the model is known to be suitable in explaining the data (F(1, 23)=8.321; p<0.008; R2=0.266). This means that coping with stress can explain 26.6% of the mental condition of vegetable farmers who experience crop failure. Farmers who fail to harvest can survive due to several factors, one of which is the religious attitude of praying and continuing to try to be one of the main things in the life of vegetable farmers so that they remain mentally healthy in the face of unwanted conditions. The dominant stress-coping component is problem-focused, oriented to the subject matter, and tends to solve the problem immediately.